2012
DOI: 10.1093/rheumatology/ker361
|View full text |Cite
|
Sign up to set email alerts
|

National prevalence of gout derived from administrative health data in Aotearoa New Zealand

Abstract: Applying algorithms to national administrative data sets provides a readily available method for estimating the prevalence of a chronic condition such as gout, where diagnosis and drug treatment are relatively specific for this disease. We have demonstrated high gout prevalence in the entire Aotearoa New Zealand population, particularly among Māori and Pacific people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
138
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(155 citation statements)
references
References 28 publications
14
138
2
1
Order By: Relevance
“…One of the most extensive epidemiological studies was undertaken by Winnard et al, who used national health data sets to sample more than 4 million of the Aoteoroa New Zealand (NZ) population; 7 this group identified a prevalence of gout of 3.75%. Both Winnard and Stamp et al also found a higher prevalence or hyperuricaemia in the NZ Maori population compared with the Non-Maori population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most extensive epidemiological studies was undertaken by Winnard et al, who used national health data sets to sample more than 4 million of the Aoteoroa New Zealand (NZ) population; 7 this group identified a prevalence of gout of 3.75%. Both Winnard and Stamp et al also found a higher prevalence or hyperuricaemia in the NZ Maori population compared with the Non-Maori population.…”
Section: Introductionmentioning
confidence: 99%
“…Both Winnard and Stamp et al also found a higher prevalence or hyperuricaemia in the NZ Maori population compared with the Non-Maori population. 7,8 In the general US population, the prevalence of medical record diagnosed gout was 3.9% and the prevalence of hyperuricaemia was 21.4%. 9 In the UK and Europe the prevalence of gout is considerably lower; a retrospective analysis of general practitioner records from 2000-2005 revealed a gout prevalence of only 1.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians are aware of the suffering of gout and of the need to provide effective education about lifestyle and medications. [14][15][16] We found interviewees were frustrated that gout was treated mainly as an acute condition rather than addressing the barriers to initiating preventive action and treating gout as a chronic disease. They felt there was inadequate time for patient education.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In 2009, a NZ study reported a nationwide prevalence of gout of 2.89% but the rate among Māori and Pacific men was at least ORIGINAL SCIENTIFIC PAPER ORIGINAL RESEARCh: CLINICAL double the national average (6.06% and 7.63%, respectively). 3 The greater prevalence among certain ethnic groups is due to genetic variation in uric acid excretion combined with factors such as lower socioeconomic status, barriers to healthcare, lower health literacy, medication non-adherence and risk averseness to treatment. 3,4 Despite longstanding, clinically useful pharmacotherapeutic agents like colchicine and allopurinol, gout remains poorly managed.…”
Section: Introductionmentioning
confidence: 99%
“…3 The greater prevalence among certain ethnic groups is due to genetic variation in uric acid excretion combined with factors such as lower socioeconomic status, barriers to healthcare, lower health literacy, medication non-adherence and risk averseness to treatment. 3,4 Despite longstanding, clinically useful pharmacotherapeutic agents like colchicine and allopurinol, gout remains poorly managed. 5 Patient views, and those of the wider community, that gout is a minor condition caused by overindulgence of food or drink and only requires medication during the acute phase, has normalized the condition and allowed it to be tolerated.…”
Section: Introductionmentioning
confidence: 99%